0% found this document useful (0 votes)
160 views3 pages

Solutions For Math 311 Assignment #1

Download as pdf or txt
Download as pdf or txt
Download as pdf or txt
You are on page 1/ 3

Solutions for Math 311 Assignment #1

(1) Show that


(a) Re(iz) = − Im(z);
(b) Im(iz) = Re(z).

Proof. Let z = x + yi with x = Re(z) and y = Im(z). Then


Re(iz) = Re(−y + xi) = −y = − Im(z) and Im(iz) = Im(−y +
xi) = x = Re(z). 

(2) Verify the associative law for multiplication of complex num-


bers. That is, show that
(z1 z2 )z3 = z1 (z2 z3 )
for all z1 , z2 , z3 ∈ C.

Proof. Let zk = xk + iyk for k = 1, 2, 3. Then


(z1 z2 )z3 = ((x1 + y1 i)(x2 + y2 i))(x3 + y3 i)
= ((x1 x2 − y1 y2 ) + i(x2 y1 + x1 y2 ))(x3 + y3 i)
= (x1 x2 x3 − x3 y1 y2 − x2 y1 y3 − x1 y2 y3 )
+ i(x2 x3 y1 + x1 x3 y2 + x1 x2 y3 − y1 y2 y3 )
and
z1 (z2 z3 ) = (x1 + y1 i)((x2 + y2 i))(x3 + y3 i))
= (x1 + y1 i)((x2 x3 − y2 y3 ) + i(x2 y3 + x3 y2 ))
= (x1 x2 x3 − x3 y1 y2 − x2 y1 y3 − x1 y2 y3 )
+ i(x2 x3 y1 + x1 x3 y2 + x1 x2 y3 − y1 y2 y3 )
Therefore,
(z1 z2 )z3 = z1 (z2 z3 )


(3) Compute
2+i
(a) ;
2−i
(b) (1 − 2i)4 .
Answer. (a) (3 + 4i)/5 (b) −7 + 24i

1
2

(4) Let f be the map sending each complex number


 
x y
z = x + yi →

−y x
Show that f (z1 z2 ) = f (z1 )f (z2 ) for all z1 , z2 ∈ C.

Proof. Let zk = xk + yk i for k = 1, 2. Then


z1 z2 = (x1 + y1 i)(x2 + y2 i) = (x1 x2 − y1 y2 ) + i(x2 y1 + x1 y2 )
and hence
 
x1 x2 − y 1 y 2 x2 y 1 + x 1 y 2
f (z1 z2 ) = .
−x2 y1 − x1 y2 x1 x2 − y1 y2
On the other hand,
    
x1 y 1 x2 y 2 x1 x2 − y1 y2 x2 y1 + x1 y2
f (z1 )f (z2 ) = = .
−y1 x1 −y2 x2 −x2 y1 − x1 y2 x1 x2 − y1 y2
Therefore, f (z1 z2 ) = f (z1 )f (z2 ). 

(5) Show that


|z1 − z2 |2 + |z1 + z2 |2 = 2(|z1 |2 + |z2 |2 )
for all z1 , z2 ∈ C.

Proof. We have
|z1 − z2 |2 + |z1 + z2 |2
= (z1 − z2 )(z1 − z2 ) + (z1 + z2 )(z1 + z2 )
= (z1 − z2 )(z 1 − z 2 ) + (z1 + z2 )(z 1 + z 2 )
= ((z1 z 1 + z2 z 2 ) − (z1 z 2 + z2 z 1 )) + ((z1 z 1 + z2 z 2 ) + (z1 z 2 + z2 z 1 ))
= 2(z1 z 1 + z2 z 2 ) = 2(|z1 |2 + |z2 |2 ).


(6) Use binomial theorem


       
n n n n n−1 n n−1 n n
(a + b) = a + a b + ... + ab + b
0 1 n−1 n
n  
X n n−k k
= a b
k=0
k
to expand√
(a) (1 + √3i)2011 ;
(b) (1 + 3i)−2011 .
3

Solution. By binomial theorem,


2011  2011 
√ 2011 X 2011 √ k X 2011 k/2 k
 
(1 + 3i) = ( 3i) = 3 i .
k=0
k k=0
k
Since ik = (−1)m for k = 2m even and ik = (−1)m i for k =
2m + 1 odd,
√ 2011 X 2011
(1 + 3i) = 3m (−1)m
0≤2m≤2011
2m

 
X 2011
+i 3m 3(−1)m
0≤2m+1≤2011
2m + 1
1005  1005 

 
X 2011 m
X 2011
= (−3) + i (−3)m 3.
m=0
2m m=0
2m + 1
Similarly,
2011 √ !2011


1 1 − 3i
(1 + 3i)−2011 = √ =
1 + 3i 4
2011 


1 X 2011
= 2011 (− 3i)k
4 k=0
k
1005  
1 X 2011
= 2011 (−3)m
4 m=0
2m
1005 


i X 2011
− 2011 (−3)m 3.
4 m=0
2m + 1

You might also like